Pengaruh Kebijakan Dukungan Pemerintah Terhadap Orientasi Kewirausahaan: Perspective interactive decision theory - Moris Adidi Yogia; Agung Wicaksono (Pelantar Press, 2025)
This study analyzes the influence of financial and non-financial support on the entrepreneurial orientation of BUMDesa using the Interactive Decision Theory approach. The hypothesis testing results indicate that both financial and non-financial support significantly affect entrepreneurial orientation, both partially and simultaneously, with an Adjusted R Square of 93.6%. These findings confirm that BUMDesa's strategic decisions are not only influenced by internal factors but also by interactions with key stakeholders, particularly the government as the primary provider of support. Theoretically, this study expands the application of Interactive Decision Theory in the context of village-based entrepreneurship by incorporating government policies as a key determinant in strategic decision-making. Furthermore, this research emphasizes that the relationship between the government and BUMDesa is dynamic and evolves alongside policy changes. From a managerial perspective, the findings provide insights for BUMDesa managers to optimize government support, as well as for policymakers in designing more adaptive and feedback-based policies. The implications of this study also highlight the importance of strengthening training programs, mentoring, and more flexible policies to create a sustainable and competitive village entrepreneurship ecosystem.